Disseminated Cryptococcosis presenting as cellulitis in a renal transplant recipient - Chaya, Ramachandraiah; Padmanabhan, Srinivasan; Anandaswamy, Venugopal; Moin, Aumir (The Journal of Infection in Developing Countries, 2013)
Cellulitis is an unusual presentation of cryptococcal infection in renal allograft recipients. In such patients, disseminated cryptococcal infection can result in significant morbidity and mortality. Patients are often treated with antibiotics before a definitive diagnosis is made, delaying appropriate therapy. We describe the case of a 43-year-old post renal transplant recipient presenting with fever and swelling in the right thigh. On physical examination, the patient was found to have features suggestive of cellulitis with minimal slurring of speech. Material obtained from incision and drainage of the wound showed yeast cells resembling Cryptococcus spp. Blood culture and cerebrospinal fluid culture were also found to have growth of Cryptococcus neoformans. He received treatment with amphotericin B 6 mg/kg daily intravenously for two weeks, then continued with fluconazole 400 mg daily for three months. The patient showed a remarkable improvement. There was no recurrence of cryptococcosis after four months of follow-up. The diagnosis of disseminated cryptococcosis should be considered in differential diagnosis of cellulitis among non HIV immunocompromised hosts. A high clinical suspicion and early initiation of therapy is needed to recognize and treat patients effectively.